Sustainable Aquaculture (Applied Environmental Science and Engineering for a Sustainable Future, 2018)
This book is about important relevant recent research topics in sustainable aquaculture practices. A critical assessment of the sustainable finishing methods and the aspect of sustainable aquaculture feed is presented in this volume. A special focus has been given to socio-economic and environmental assessment of aquaculture practices and analysis of carbon footprint under an intensive aquaculture regime. Aquaponics as a niche for sustainable modern aquaculture has been highlighted. The effect of use of pharmaceuticals to prevent fish disease on the surrounding marine environment is an emerging area of concern, and a critical discussion on this aspect is included in the book. The spread of organic waste and nutrients released by fish farms to natural water bodies has raised considerable concerns. Therefore the methods to prevent their dispersion and removal (treatment) have been comprehensively covered in this book. This book is an essential read for academician, researchers, and policy makers in the field of aquaculture. .